Nilai- nilai pendidikan Islam dalam ajaran Ki Hajar Dewantara - Nasrullah Nasrullah; Hanif Cahyo Adi (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Education is a golden bridge to change. Through education, someone teaches how to change things. This study aims to determine the values of Islamic education in the teachings of Ki Hajar Dewantoro. This research uses library research (library research), and the type of analysis descriptive approach. The main data source uses the first part of Ki Hadjar Dewantara's book: education, while the secondary data is in the form of supporting books, as well as scientific journals related to research themes. Collecting data using documentation in the form of a main data checklist. Data analysis used content analysis in a systematic way, then given a thorough interpretation. The results of the study show that the